Potensi Pemanfaatan Sumber Tenaga Energi Baru Terbarukan Di Desa Sukamandi Kabupaten Subang - Budi Harja, Herman; Ariyani, Emma Dwi; Muldani Hendrawan, Yogi; Riduansyah, Rayadi (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The availability of electrical energy significantly affects the survival of human life. Sources of electrical energy can be obtained from non-renewable energy sources, including oil and coal, besides that electrical energy can also be obtained from renewable energy sources, including the potential energy of water, air, and light. This paper describes a study on the utilization of renewable energy potential in Sukamandi Village, Sagalaherang District, Subang Regency. This study was conducted through several focus activities, namely observation and measurement, especially on the potential energy of water, wind and solar energy available in Sukamandi Village. The results of the study of observations and measurements show that the potential for water energy in the Curug Cibingbin waterfall is 334 Watt, the potential for wind energy in Bukit Jamali is 129 Watt, and the potential for solar energy in Bukit Jamali is 9,4503 Watt for potential solar energy. Therefore, a more comprehensive study that can be directly applied is the design of making energy conversion devices from the three energy potentials that have been studied